Seeing the World Through Orthopaedic Eyes: The Experience of Being an Orthopaedic Nurse: A Hermeneutic Study - Blake-Palmer, Elizabeth (Auckland University of Technology, 2007)
This study explores the experience of being an orthopaedic nurse. As an orthopaedic nurse I had concerns that the validity of orthopaedic nursing as a unique scope of practice was being questioned. In this thesis, the case for orthopaedic nursing is argued, by showing it as a specialty in its own right. A qualitative approach informed by my interpretation of philosophical hermeneutics as articulated by Heidegger (1927/1962) and Gadamer (1976; 1989) was undertaken. Phenomenology seeks to uncover 'taken-for-granted' meanings in everyday experience and hermeneutic research recognises that the historical and cultural horizons of participants and researcher influence the interpretation. Eight nurses working in various orthopaedic settings were interviewed. Data was analysed using the interpretive thematic approach described by van Manen (1990). The nurses' stories from practice yielded two essential themes, 'being part', and 'gaining and maintaining integrity'. These themes interrelate and together reveal meanings and insights about being an orthopaedic nurse. 'Being part', shows the essential nature of relationships between orthopaedic nurses and others. 'Gaining and maintaining integrity' describes the embodied nature of the phenomenon. The overall thematic finding 'seeing the world through orthopaedic eyes' reveals the nature of orthopaedic nursing as a unique scope of practice.